Bisnis Iklan Media Cetak dalam Mensejahterakan Karyawan - Asmaunizar; Yeni Muslinda (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Print media advertising helps entrepreneurs market their products or services. Advertising provides a sizable income for the company for employee welfare and media development. It is interesting to know how the forms and benefits derived from display advertising in print media, and how the contribution of display advertising to print media in employee welfare. This research was conducted by field research. Field data were analyzed using descriptive-analysis method. The results showed that the benefits derived from display advertising on print media were in two aspects. First, the advantages in the area of ordering. Ordering display advertisements in print media is relatively quite a lot. Second, in the aspect of receiving profits in the form of turnover per day from display advertising. The advantage of display advertising business depends on the number of parties who install and utilize advertising services. The contribution of display advertising business to print media in employee welfare can be seen from two indicators. First, employee satisfaction in working in print media. Second, the income obtained from the display advertising business is seen to have been able to meet the needs of the family.